Can We Reduce Secondary Surgical Interventions and Length of Hospitalization in Percutaneous Nephrolithotomy? - Deliktas, Hasan; Yapici, Onur; Ozen, Utku; Yalcin, Engin; Sahin, Hayrettin (Urology Journal, 2014)
Abstract Purpose: To evaluate the success and complication rates of percutaneous nephrolithotomy (PNL) operations and to determine the effect of postoperative late removal of an open-end ureter catheter on hospital stay and on secondary interventions. Materials and Methods: The records of 198 patients (97 female, 101 male) who had PNL between May 2009 and February 2012 were retrospectively reviewed. The open-end ureter catheter which was placed during the operation was removed at the end of the operation in the first 53 patients ( group 1) and 12 hours after the nephrostomy catheter in 145 patients ( group 2). Results: PNL intervention was performed in 198 patients with a mean age of 40.83 ± 13.64 years and mean stone load of 9.82 ± 5.37cm2 (range 2 to 26 cm2). When clinically insignificant stone pieces < 4 mm were accepted as successful, the total success rate was 80.80 % (79.2% in group1 and 81.4% in group 2, P = .50). The hospitalization period was significantly reduced in group 2 (3.45 ± 0.95 days vs. 2.61 ± 0.65 days; P = .006). While secondary surgical intervention was not necessary in any of the patients in group 2 (0.0%), but 4 patients (7.5%) required ureterorenoscopy plus double-J stent placement following the primary procedure in group 1 (P = .006). Conclusion: PNL is a safe procedure with a high success rate and a short hospitalization period. There was a significant decrease in the hospitalization period and secondary surgical intervention rates with the postoperative late removal of the open-end ureter catheter.